Given the expression:
![3x^4+5x^3+px^2+qx+6](https://img.qammunity.org/2023/formulas/mathematics/college/3kbap0s0a08gaedly72cgtk6ldllv92wyn.png)
Factors of the expression are:
(x - 2) and (x +3).
Let's find the values of p and q.
To solve for p and q, take the following steps:
Step 1:
Equate the factors to zero and solve for x.
x - 2 = 0
Add 2 to both sides:
x - 2 + 2 = 0 + 2
x = 2
x + 3 = 0
Subtract 3 from both sides:
x+ 3 - 3 = 0 - 3
x = -3
Thus, we have:
x = 2 and -3
Step 2:
Now, solve the expression for f(2) and f(-3).
We have:
![\begin{gathered} f(2)=3(2)^4+5(2)^3+p(2)^2+q(2)+6 \\ \\ f(2)=48+40+4q+2q+6 \\ \text{Combine like terms:} \\ f(2)=48+40+6+4p+2q \\ \\ f(2)=94+4p+2q \\ \\ \text{Equate to zero:} \\ 94+4p+2q=0 \\ \\ 4p-2q=-94 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2z7ql6dkok145trs9fvmr7zkw93v5svmqo.png)
Solve for f(-3):
![\begin{gathered} f(-3)=3(-3)^4+5(-3)^3+p(-3)^2+q(-3)+6 \\ \\ f(-3)=243-135+9p-3q+6 \\ \\ f(-3)=9p-3q+114 \\ \\ 9p-3q=-114 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w0kzzhrpqee9itik48hd0i9m24gmnjo2gi.png)
Now, we have the set of equations:
4p - 2q = -94..................equation 1
9p - 3q = - 114..................equation 2
Step 3:
Solve the set of equations simultaneously using the elimination method.
4p - 2q = -94
9p - 3q = -114
Multilply all terms in equation 1 by -3 and equation two by 2:
4p(-3) - 2q(-3) = -94(-3)
9p(2) - 3q(2) = -114(2)
-12p + 6q = 282................equation 3
18p - 6q = -228,...............equation 4
Add both equation 3 and 4
-12p + 6q = 282
+ 18p - 6q = -228
--------------------------------
6p + 0 = 54
6p = 54
Divide both sides by 6:
![\begin{gathered} (6p)/(6)=(54)/(6) \\ \\ p=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/geuna9cthvu247bfajsf8l5dtc7gnn626t.png)
Substitute 9 for p in equation 1:
4p - 2q = -94
4(9) - 2q = -94
36 - 2q = -94
Subtract 36 from both sides:
36 - 36 - 2q = -94 - 36
-2q = -130
Divide both sides by -2:
![\begin{gathered} (-2q)/(-2)=(-130)/(-2) \\ \\ q=65 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8f3u3a02acqljzx6a69cwjnz0iq245pbym.png)
Therefore, the values of p and q are:
p = 9
q = 65
ANSWER:
p = 9 and q = 65